Quadratic roots

Let r'r' be a root of the equation :

x2+2x+6=0x^{2}+2x+6=0

Then find the value of: (r+2)(r+3)(r+4)(r+5)(r+2)(r+3)(r+4)(r+5)

I wan't to know all possible approaches to this problem.

Would be gratified if got some responses :D


DETAILS\text{DETAILS}:

This appeared in KVPY SA this year(today :P)

#Algebra #KVPY #ProblemSolving #Quadratic

Note by Aritra Jana
6 years, 7 months ago

No vote yet
1 vote

  Easy Math Editor

This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.

When posting on Brilliant:

  • Use the emojis to react to an explanation, whether you're congratulating a job well done , or just really confused .
  • Ask specific questions about the challenge or the steps in somebody's explanation. Well-posed questions can add a lot to the discussion, but posting "I don't understand!" doesn't help anyone.
  • Try to contribute something new to the discussion, whether it is an extension, generalization or other idea related to the challenge.
  • Stay on topic — we're all here to learn more about math and science, not to hear about your favorite get-rich-quick scheme or current world events.

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 2×3 2 \times 3
2^{34} 234 2^{34}
a_{i-1} ai1 a_{i-1}
\frac{2}{3} 23 \frac{2}{3}
\sqrt{2} 2 \sqrt{2}
\sum_{i=1}^3 i=13 \sum_{i=1}^3
\sin \theta sinθ \sin \theta
\boxed{123} 123 \boxed{123}

Comments

As rr is the root of the given equation, r2+2r+6=0r^{2}+2r+6=0 ...... (1)

And

(r+2)(r+3)(r+4)(r+5)(r+2)(r+3)(r+4)(r+5) = (r+2)(r+5)(r+4)(r+3)(r+2)(r+5)(r+4)(r+3)

=(r2+7r+10)=({r}^{2}+7r+10) (r2+7r+12)(r^{2}+7r+12)

Substituting value of r2r^{2} from (1),

=(5r+4)(5r+6)=(5r+4)(5r+6)

=(25r2+50r+24)=(25{r}^{2}+50r+24)

Again substituting value of r2r^{2} from (1),

=126=\boxed{-126}

Karthik Sharma - 6 years, 7 months ago

Log in to reply

Manipulation at its best.

Krishna Ar - 6 years, 6 months ago

x2+2x+1+5=0 x^{2} + 2x + 1 + 5 =0

(x+1)2=5 (x + 1)^{2} = -5

x=1±i5 x = -1 \pm i\sqrt{5}

( since any root is asked)

thus

(1+i5+2)(1+i5+3)(1+i5+4)(1+i5+5) (- 1 + i\sqrt{5} + 2)( - 1 + i\sqrt{5} + 3)( - 1 + i\sqrt{5} + 4)( - 1 + i\sqrt{5} + 5)

=(1+i5)(2+i5)(3+i5)(4+i5)= (1 + i\sqrt{5})(2 + i\sqrt{5})(3 + i\sqrt{5})(4 + i\sqrt{5})

=(1+i5)(4+i5)(2+i5)(3+i5) = (1 + i\sqrt{5})(4 + i\sqrt{5})(2 + i\sqrt{5})(3 + i\sqrt{5})

=(1+5i5)(1+5i5) = ( -1 + 5i\sqrt{5})(1 + 5i\sqrt{5})

=126 = -126

U Z - 6 years, 7 months ago

Just factorise it and substitute the value of 'r' in the quadratic equation obtained.

Manmeswar Patnaik - 6 years, 7 months ago

SORRY ITS-126 JUST SOLVED

Navdeep Nainwal - 6 years, 7 months ago
×

Problem Loading...

Note Loading...

Set Loading...